Zinc‐Ion Batteries: A Chemically Self‐Charging Flexible Solid‐State Zinc‐Ion Battery Based on VO2 Cathode and Polyacrylamide–Chitin Nanofiber Hydrogel Electrolyte (Adv. Energy Mater. 25/2021). Issue 25 (8th July 2021) - Liu, Chaozheng; Xu, Wangwang; Mei, Changtong; Li, Meichun; Chen, Weimin; Hong, Shu; Kim, Won‐Yeong; Lee, Sang‐young; Wu, Qinglin
Abstract : In article number 2003902, Wangwang Xu, Changtong Mei, Qinglin Wu and co‐workers show that the robust tunnel structure of a vanadium dioxide cathode and the network of a polyacrylamide‐chitin nanofiber hydrogel electrolyte provide efficient pathways for ion diffusion, leading to superior electrochemical performance of the corresponding solid‐state zinc ion batteries (ssZIBs). The flexible ssZIBs demonstrate excellent self‐rechargeability and superior reusability, which provides a facile route to portable self‐powered systems.